2007
DOI: 10.1145/1272848.1272876
|View full text |Cite
|
Sign up to set email alerts
|

Nifty reflections

Abstract: Nifty Assignments are nice and everything, but it's natural to wonder: Where are Nifty Assignments weakest?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Previous work has also examined novice behavior when solving short programming exercises, similar to those found in CodingBat [16] and CloudCoder. An example is the work of Denny et.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has also examined novice behavior when solving short programming exercises, similar to those found in CodingBat [16] and CloudCoder. An example is the work of Denny et.…”
Section: Related Workmentioning
confidence: 99%
“…Request permissions from permissions@acm.org. as CodingBat [16] and CloudCoder [10], can be a useful way for instructors to provide students with additional opportunities to practice basic concepts and techniques with the ultimate goal being (hopefully) to help students achieve better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent web-based drill and practice framework is Parlante's CodingBat tool (previously named JavaBat) [9]. Students using CodingBat are presented with a description of a problem along with a corresponding method header.…”
Section: Related Workmentioning
confidence: 99%
“…Recent educational research in various disciplines has shown that student generated questions are of acceptably high quality for such purposes [1,15]. Specifically in computer science education, various tools have been developed which provide students with banks of instructor-created exercises with which to practice [14,13]. In light of the benefits associated with generating questions, we encourage designers of such tools to consider approaches that would allow students to develop their own exercises and contribute them to these platforms.…”
Section: Discussionmentioning
confidence: 99%